Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada Perusahaan Daerah Air Minum (Pdam) Bandarmasih Kota Banjarmasin - Ihsan, Muhammad; Yunida, Riswan; Huwaida, Hikmayanti; Shintia, Novi; Amelia, Rini; Wahyu Wardhana, Muhammad (P3M Politeknik Negeri Banjarmasin, 2023)
The aims of this research are: (1) To find out whether service quality (tangible, reliability, responsiveness, assurance, empathy) has a simultaneous effect on customer satisfaction of the Bandarmasih Regional Drinking Water Company (PDAM) in Banjarmasin City. (2) To find out whether service quality (tangible) has a partial effect on customer satisfaction of PDAM Bandarmasih, Banjarmasin City. (3) To find out whether service quality (reliability) has a partial effect on customer satisfaction of PDAM Bandarmasih, Banjarmasin City. (4) To find out whether service quality (responsiveness) has a partial effect on customer satisfaction of PDAM Bandarmasih, Banjarmasin City. (5) To find out whether service quality (assurance) has a partial effect on customer satisfaction (PDAM) Bandarmasih, Banjarmasin City. (6) To find out whether service quality (emphaty) has a partial effect on customer satisfaction of PDAM Bandarmasih, Banjarmasin City. (7) To find out which variables of service quality (tangible, reliability, responsiveness, assurance, empathy) are most dominant in influencing customer satisfaction of PDAM Bandarmasih, Banjarmasin City. The method used in this study is a quantitative research method with multiple linear regression. The findings of this study indicate that: (1) The independent variables namely service quality (tangible, reliability, responsiveness, assurance, empathy) simultaneously affect customer satisfaction by 74.2%, while the remaining 25.8% are influenced by other variables outside this research. (2) Tangible variable (X1) has no significant effect partially on customer satisfaction (Y) with a Tcount of 0.988. (3) The realibility variable (X2) has a partially significant effect on customer satisfaction (Y) with a Tcount of 3.196 (4) The responsiveness variable (X3) has no partially significant effect on customer satisfaction (Y) with a Tcount of -1.506. (5) Assurance variable (X4) has no significant effect partially on customer satisfaction (Y) with a Tcount of 0.443. (6) The empathy variable (X5) has a partially significant effect on customer satisfaction (Y) with a Tcount of 4.999. (7) the empathy variable (X5) has the most dominant influence on customer satisfaction (Y) with the highest r2 value of 0.209 or 20.9%.